CDH1 Gene and Hereditary Diffuse Gastric Cancer Syndrome: Molecular and Histological Alterations and Implications for Diagnosis And Treatment - Luo, Wenyi; Fedda, Faysal; Lynch, Patrick; Tan, Dongfeng (Frontiers in Pharmacology, 2018)
Gastric cancer, a group of common malignancies, results in the most cancer mortality worldwide after only lung and colorectal cancer. Although familial gastric cancers have long been recognized, it was not until recently that they were discovered to be associated with mutations of specific genes. Mutations of CDH1, the gene encoding E-cadherin, are the most common germline mutations detected in gastric cancer and underlie hereditary diffuse gastric cancer (HDGC) syndrome. All reported HDGCs are the pure diffuse type by Lauren classification and are associated with dismal prognosis once the tumor invades the submucosa. Because CDH1 germline mutations are inherited in an autosomal-dominant fashion and have high penetrance, the International Gastric Cancer Linkage Consortium (IGCLC) developed criteria to facilitate the screening of CDH1 mutation carriers; these criteria have been proven to have excellent sensitivity and specificity. Recent histologic studies suggest that HDGC progresses through several stages. Even when the tumor becomes “invasive” in lamina propria, it may stay indolent for a long time. However, the molecular mechanisms that induce the transitions between stages and determine the length of the indolent phase remain to be determined. Although the standard management for CDH1 mutation carriers is prophylactic total gastrectomy, many questions must be answered before the surgery can be done. These include the optimal surveillance strategy, the best strategy to choose surgical candidates, and the ideal time to perform surgery. In addition to increasing the risk of gastric cancer, CDH1 germline mutations also increase the risk of invasive lobular carcinoma of the breast, and possibly colorectal adenocarcinoma, and are associated with blepharocheilodontic syndrome (a congenital development disorder). However, the optimal management of these conditions is less established owing to insufficient data regarding the risk of cancer development. This review focuses on molecular and histological findings in HDGC, as opposed to sporadic diffuse gastric cancer, and their implications for the management of CDH1 mutation carriers and the diagnosis and treatment of HDGC. Other conditions associated with CDH1 germline mutations and future research directions are also discussed.